PAR1 signaling regulates the retention and recruitment of EPCR-expressing bone marrow hematopoietic stem cells - Gur-Cohen, Shiri; Itkin, Tomer; Chakrabarty, Sagarika; Graf, Claudine; Kollet, Orit; Ludin, Aya; Golan, Karin; Kalinkovich, Alexander; Ledergor, Guy; Wong, Eitan; Niemeyer, Elisabeth; Porat, Ziv; et al. (Nature medicine, 2015)
Factors traditionally associated with coagulation and inflammation, such as thrombin, PAR1, aPC and EPCR, also independently control the nitric oxide production switch in hematopoietic stem cells, thereby regulating EPCR-expressing stem cell adhesion and retention in the bone marrow or recruitment to the blood. Retention of long-term repopulating hematopoietic stem cells (LT-HSCs) in the bone marrow is essential for hematopoiesis and for protection from myelotoxic injury. We report that signaling cascades that are traditionally viewed as coagulation related also control retention of endothelial protein C receptor–positive (EPCR + ) LT-HSCs in the bone marrow and their recruitment to the blood via two pathways mediated by protease activated receptor 1 (PAR1). Thrombin-PAR1 signaling induces nitric oxide (NO) production, leading to EPCR shedding mediated by tumor necrosis factor-α–converting enzyme (TACE), enhanced CXCL12-CXCR4–induced motility and rapid stem and progenitor cell mobilization. Conversely, bone marrow blood vessels provide a microenvironment enriched with activated protein C (aPC) that retains EPCR + LT-HSCs by limiting NO generation, reducing Cdc42 activity and enhancing integrin VLA4 affinity and adhesion. Inhibition of NO production by aPC-EPCR-PAR1 signaling reduces progenitor cell egress from the bone marrow, increases retention of bone marrow NO low EPCR + LT-HSCs and protects mice from chemotherapy-induced hematological failure and death. Our study reveals new roles for PAR1 and EPCR in controlling NO production to balance maintenance and recruitment of bone marrow EPCR + LT-HSCs, with potential clinical relevance for stem cell transplantation.